Service Quality of Boarding Madrasah: Integration of The Ministry of Religious Affairs’ PAI Curriculum and Student Guidance Management - Hasri Nur Azizah; Im Young Ho; Moh Ali; Qonita Nurshabrina (ADARA, 2026)
This study investigates the service quality of boarding madrasah through the systematic integration of the Islamic Religious Education (PAI) curriculum issued by the Ministry of Religious Affairs with the student guidance management programme at Ma’had Insan Cendikia MTs Negeri 1 Banyumas. Boarding madrasahs confront two simultaneous demands: compliance with national curriculum mandates and the operational management of student residential life. A qualitative approach grounded in interpretive phenomenology was employed, involving nine purposively selected key informants drawn from student, dormitory supervisor, and parent groups. Data were gathered through in-depth interviews, participatory observation, and document review, and were subsequently analysed using thematic analysis. The findings demonstrate that: (1) integrating the PAI curriculum under KMA 183/2019 with the residential curriculum produces a holistic educational model that aligns formal instruction, intensive Qur’anic memorisation (tahfidz), and tiered character development; (2) student guidance management operates through a structured and transparent communication system that fosters triangular collaboration among students, families, and the ma’had; (3) service quality is evidenced by the institution’s capacity to facilitate students’ developmental progress across three sequential phases—initial adjustment, stabilisation, and self-transformation underpinned by consistent family support; and (4) the admission of the first graduating cohort to leading educational institutions validates the effectiveness of this integration model. The study contributes a theoretically grounded triangular-collaboration curriculum model and offers practical recommendations for developing holistic support systems within boarding madrasah settings.